Lectin microarrays for glycoproteomics: an overview of their use and potential. (2nd January 2020) - Yu, Hanjie; Shu, Jian; Li, Zheng
ABSTRACT: Introduction : Glycoproteomics is an important subdiscipline of proteomics, focusing on the role of protein glycosylation in various biological processes. Protein glycosylation is the enzymatic addition of sugars or oligosaccharides to proteins. Altered glycosylation often occurs in the early stages of disease development, for example, certain tumor-associated glycans have been shown to be expressed in precursor lesions of different types of cancer, making them powerful early diagnostic markers. Lectin microarrays have become a powerful tool for both the study of glycosylation and the diagnosis of various diseases including cancer. Areas covered : This review will discuss the most useful features of lectin microarrays, such as their technological advances, their capability for parallel/high-throughput analysis for the important glycopatterns of glycoprotein, and an overview of their use for glycosylation analysis of various complex protein samples, as well as their diagnostic potential in various diseases. Expert opinion : Lectin microarrays have proved to be useful in studying multiple lectin–glycan interactions in a single experiment and, with the advances made in the field, hold a promise of enabling glycopatterns of diseases in a fast and efficient manner. Lectin microarrays will become increasingly powerful early diagnostic tool for a variety of conditions.